2018
DOI: 10.1371/journal.pone.0195485
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for hand grip strength in the South Korean population

Abstract: ObjectiveTo establish reference values for hand grip strength (HGS) in a healthy Korean population and to identify the dependent anthropometric variables that affect HGS.MethodsBased on the sixth Korea National Health and Nutrition Examination Survey from 2014 to 2015, we analyzed the HGS data of 7,969 South Koreans. Individuals with specific chronic diseases and who reported poor subjective health status were excluded to ensure a healthy population sample. Means with standard deviations (SDs) and 95% confiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
78
2
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 47 publications
(60 reference statements)
13
78
2
4
Order By: Relevance
“…We also compared our results with the data obtained from other studies in Taiwan and determined that our mean values were similar to those reported by Wu et al in 2009 20 , but slightly lower than the data reported by Liao et al in 2014 23 . A comparison of our data with those reported in other Asian regions revealed that the mean values obtained in our study were lower than those obtained in the studies by Seino et al in Japan and Kim et al in Korea 8,24 , but were similar to those of another study reported by Ong et al in Singapore in 2017 7 . It has been proposed that global variations in the norms of HGS were present, which might be attributable to the status of development 5 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We also compared our results with the data obtained from other studies in Taiwan and determined that our mean values were similar to those reported by Wu et al in 2009 20 , but slightly lower than the data reported by Liao et al in 2014 23 . A comparison of our data with those reported in other Asian regions revealed that the mean values obtained in our study were lower than those obtained in the studies by Seino et al in Japan and Kim et al in Korea 8,24 , but were similar to those of another study reported by Ong et al in Singapore in 2017 7 . It has been proposed that global variations in the norms of HGS were present, which might be attributable to the status of development 5 .…”
Section: Discussionsupporting
confidence: 82%
“…HGS among elderly people in Singapore was also lower than that among elderly people in some Western countries 7 . Kim et al demonstrated that among Koreans HGS peaked at 35-39 years of age and thereafter decreased in both sexes 8 . Additional studies are warranted, especially in other regions of Asia, to evaluate the normative data of HGS.…”
mentioning
confidence: 99%
“…In the present study, the mean HGS value of cancer survivors by age was not different from that previously reported for the Korean general population 19 20. The reasons might be that patients with poor physical condition were excluded by chance due to the nature of the KNHANES or that most cancer survivors have well-managed physical function.…”
Section: Discussioncontrasting
confidence: 69%
“…These cut‐off thresholds are derived from the Italian InChianti study by Lauratani et al In contrast, the EWGSOP consensus recommends use of population‐specific cut‐off points for handgrip strength where available (EWGSOP1), rather than the other populations (EWGSOP1). After publication of the EWGSOP consensus, other research groups defined population‐specific handgrip strength cut‐off values . These include handgrip strength cut‐off values of ≤ 15 and ≤ 27 in the Chilean population, <16 and <27 kg in the British population, <16.8 kg and <28.9 kg in the Korean population, and <22 kg and <32 kg in the Turkish population in men and women, respectively, which was reported by our group .…”
supporting
confidence: 64%